Influence of Ion Pairs and Activity on the Index of Irrigation Water Quality Relying on Some Modern Terms in Erbil Governorate. * - Kazhin Sarbaz Rajab; Akram Othman Esmail (Zanco Journal of Pure and Applied Sciences, 2022)
The research was done in Erbil governorate, Iraqi Kurdistan Region in both times of sampling (June and October 2020) to determine a quality index of irrigation water (IWQI) for 354 water samples depending on (EC, SAR, CROSSo, MCAR, SP, RSC) parameters before and after correcting ion pairs and ion pairs plus activity. The results indicated the effect of correcting ion pairs and activity on the values of the above parameters which caused an increase in the values of SAR and CROSSo for different water resources in both wet and dry seasons. On the other hand, the above corrections caused a decrease in MCAR, SP, and negative value of RSC, for the water of rivers, springs, and wells in both seasons of sampling. The studied water resources were classified using IWQI depending on the above parameters in both seasons. The results indicated that 74 and 55 water samples have excellent class before correcting ion pairs and activity for wet and dry season respectively, while the water for 77 and 54 samples had excellent class after correcting ion pairs plus activity for both seasons respectively. While (27, 39) and (28, 39) water samples had the good class before and after correcting ion pairs and activity for both seasons respectively. Water samples for (14, 10) and (15, 5) locations have an average class for the wet and dry season before and after correcting ion pairs plus activity. The 62 and 73 water samples had poor class in wet and dry seasons before correcting ion pairs plus activity respectively and 57 and 79 samples had the same class after correcting ion pairs plus activity for both seasons respectively. REFERENCES ADAMS, F. 1971. Ionic concentration and activities in soil solutions. Soil Sci. Amer. Proc.35. pp: 420-426. ALANI, A. S. 2015. The Chemical composition of irrigation water and it is effect on ion pairing, some chemical properties of soil and plant growth, Erbil-Kurdistan region-Iraq. M.Sc. Thesis. College of Agri. Salahaddin University. Iraq. pp: 58-68. AL-SAFFAWI, A.Y.T., ABUBAKAR, B.I., ABBASS, L.Y. and MONGUNO, A.K., 2020. Assessment of groundwater quality for irrigation using water quality index (IWQ Index) in Al-Kasik Subdistrict Northwestern, Iraq. Nigerian Journal of Technology, 39(2), pp. 632-638. AMEEN, H.A., 2019. Springwater quality assessment using water quality index in villages of Barwari Bala, Duhok, Kurdistan Region, Iraq. Appl. water sci. 9:176https://doi.org/10.1007/s13201-019-1080-z. AMERICAN PUBLIC HEALTH ASSOCIATION (APHA) 2001. Standard methods for the examination of water and wastewater. 20th Ed. A. P. H. A., Washington. DONEEN, L.D., 1954. Salination of soil by salts in the irrigation water. Eos, Transactions American Geophysical Union, 35(6), 943-.950. ESMAIL, A. O. 2001. Role of ionic activity in relation between ionic strength and electrical conductivity of ground water in Arbil plain. Journal of Dohuk Univ. 2:73-77. (In Arabic). ESMAIL, A. O. 1992. Effect of Composition and ion pairs in irrigation water on soil and plant. Ph.D. Dissertation, College of Agriculture, University of Baghdad, Iraq. ESMAIL, A.O. and SALIH, H.O., 2014. The role of ion pairs and ion activity in classification of ground waters for irrigation in Erbil plain. Journal of Zankoy Sulaimani-Part A, Special, (16), p.177. GHOPE, N.S., DANDGE, K.P., INGLE, S.T. and ROKADE, V.M., 2019. GIS Application for Assessment and Mapping of Irrigation Water Quality in Piedmont Plain of Jalgaon District, Maharashtra, India. International Journal, 8(1), pp. 2997-3010. HANNA, N.S., SHEKHA, Y.A. and ALI, L.A.Q., 2019. Water quality assessment of Rawanduz River and Gali Ali Beg stream by applied CCME WQI with survey aquatic insects (Ephemeroptera). Iraqi Journal of Science, pp. 2550-2560. MAIA, C.E., BRAGA, A.Q.C., DA SILVA NETO, J.M. and BRAGA, E.D.C., 2020. Irrigation water quality using cation ratio and sodium adsorption ratio in the baixo Açu Region. Brazilian Journal of Animal and Environmental Research, 3(4), pp. 2928-2934. MAIA, C.E. and RODRIGUES, K.K.R.D.P., 2012. Proposal for an index to classify irrigation water quality: a case study in northeastern Brazil. Revista Brasileira de Ciência do Solo, 36, pp. 823-830. MAM RASUL, Gh. A. 2000. Study of water quality and its effect on nutrients availability for corn in Sulaimani region. MSc. Thesis. College of agriculture /Sulaimani Univ. /Iraq. MEIRELES, A.C.M., ANDRADE, E.M.D., CHAVES, L.C.G., FRISCHKORN, H. and CRISOSTOMO, L.A., 2010. A new proposal of the classification of irrigation water. Revista Ciência Agronômica, 41, pp. 349-357. OTHMAN, B.A. and IBRAHIM, E.S., 2021. Assessment of Groundwater Quality over the Erbil Plain Based on Water Quality Index. Zanco Journal of Pure and Applied Sciences, 33(s1), pp. 1-10. RAJAB, K. S 2015, Classification of some groundwater for irrigation Purpose Depending on IWQI. M.Sc. Thesis, College of Agri. Univ. of Salahaddin Erbil Kurdistan-Iraq). RICHARDS, L.A., 1954. Diagnosis and improvement of saline and alkaline soils-United States Department of Agriculture Handbook No. 60. United States Government Printing Office, Washington DC. SALIH, H. O. 2008. The role of ionic activity in classification of some groundwater on soil chemical properties and wheat yield in Erbil plain. M.Sc. Thesis. College of Agri. Salahaddin University-Erbil. SARKAR, A.A. and HASSAN, A.A., 2006. Water quality assessment of a groundwater basin in Bangladesh for irrigation use. Pakistan Journal of Biological Science, volume 9, Issue: 9 pages. 1677 – 1684. SHEKHA, Y.A., 2008. The effect of Erbil city wastewater discharge on water quality of Greater Zab River, and the risks of irrigation. PhD, university of Baghdad. UNITED NATIONS EDUCATION, SCIENTIFIC AND CULTURAL ORGANIZATION (UNESCO). 2001. Food supply balance sheet. The Eco. Soc. of Amer. WWW.frontiersinecology.Org. VINOD, J., SATISH, D. and SAPANA, G., 2013. Assessment of water quality index of industrial area surface water samples. International Journal of ChemTech Research, 5(1), pp.278-283. WILCOX, L.V., 1955. Classification and use of irrigation waters (No. 969). US Department of Agriculture.